Metal hypersensitivity and pro-inflammatory cytokine production in patients with failed orthopedic implants: A case-control study - Podzimek, Stepan; Himmlova, Lucie; Janatova, Tatjana; Bjørklund, Geir; Vrbova, Radka; Janovska, Marketa; Peana, Massimiliano; Chasapis, Christos T; Vinsu, Alex; Prochazkova, Jarmila; Duskova, Jana (Clinical immunology, 2022)
Orthopedic implants heal well without complications in most patients but fail for unclear reasons in some individuals. This study determined the relevance of metal hypersensitivity in patients with failed orthopedic implants and those requiring orthopedic implant surgery. The study included 35 patients with failed orthopedic implants and 15 subjects scheduled for orthopedic implant surgery. The production of selected pro-inflammatory cytokines was measured in patients with failed orthopedic implants. Metal hypersensitivity was measured in all subjects using the MELISA® test. Of common metals in orthopedic alloys, the patients with failed orthopedic implants responded most frequently to nickel, chromium, titanium, iron, and molybdenum. Hypersensitivity to metals found in implants was measured in 40% of patients with failed implants. The study also showed that titanium exposure in patients with titanium hypersensitivity might lead to implant failure. Metal hypersensitivity testing should be offered to patients before surgery to minimize the risk of implant failure.
Keywords: titan; Metals; cytokiny; Prostheses and Implants; alergie; lidé; protézy a implantáty; Titanium; Hypersensitivity; Cytokines; Case-Control Studies; studie případů a kontrol; kovy; Humans